Ensaio sobre a chuva: procedimento e liquidez - Paula, Carlos Eduardo Ferreira (Revista do Colóquio, 2021)
This work aims to reflect on the use of water as plastic and poetic material. Using the Argentine writer Cesar Aira's notion of procedure, he seeks to look at water in the work of three artists: Oswaldo Goeldi, Brígida Baltar and Nuno Ramos. Water as an element of nature used in culture as a sign of the emotional and the fluidity of life generates reflections from the work of artists such as: death and the sublime passing of time. To instigate the procedure of the artists when using water in some way, contributes for us to have an idea of ​​the sophistication of the poetic game.